A common molecular logic determines embryonic stem cell self‐renewal and reprogramming. (27th November 2018) - Dunn, Sara‐Jane; Li, Meng Amy; Carbognin, Elena; Smith, Austin; Martello, Graziano
Abstract: During differentiation and reprogramming, new cell identities are generated by reconfiguration of gene regulatory networks. Here, we combined automated formal reasoning with experimentation to expose the logic of network activation during induction of naïve pluripotency. We find that a Boolean network architecture defined for maintenance of naïve state embryonic stem cells (ESC) also explains transcription factor behaviour and potency during resetting from primed pluripotency. Computationally identified gene activation trajectories were experimentally substantiated at single‐cell resolution by RT–qPCR. Contingency of factor availability explains the counterintuitive observation that Klf2, which is dispensable for ESC maintenance, is required during resetting. We tested 124 predictions formulated by the dynamic network, finding a predictive accuracy of 77.4%. Finally, we show that this network explains and predicts experimental observations of somatic cell reprogramming. We conclude that a common deterministic program of gene regulation is sufficient to govern maintenance and induction of naïve pluripotency. The tools exemplified here could be broadly applied to delineate dynamic networks underlying cell fate transitions. Synopsis: While a minimal interaction network of transcription factors recapitulates naïve state maintenance of embryonic stem cells, our understanding of the logic controlling acquisition of pluripotency remains fragmentary. In this study, an iterative, computational‐experimental approach reveals that a common network governs both maintenance and installation of naïve pluripotency. Formal verification of Boolean network dynamics uncovers the network logic governing induction of naïve pluripotency from murine primed epiblast stem cells (EpiSC) and somatic cells. Model predictions identify factors to enhance or be required for reprogramming. Dual combinations of factors act synergistically and sequentially to enhance EpiSC resetting. Network architecture and update rules predict gene activation dynamics substantiated by single‐cell gene expression analysis. Individual cells follow a deterministic trajectory in the final stage of productive reprogramming. Abstract : A single transcription factor program governs maintenance and induction of naïve pluripotency.